Distribution. E in Cricetidae ... - Wilson, Don E.; Mittermeier, Russell A.; Thomas E. Lacher, Jr (Zenodo, 2017)
Distribution. E Ukraine and Crimea, C, E & S European Russia, Georgia, E Turkey, Armenia, Azerbaijan, extreme NW Iran, N & E Kazakhstan, S Siberia (as far E as Tomsk and Kemerovo regions, and W Tuva), NW Mongolia, and NW China (Xinjiang). ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 352, DOI: 10.5281/zenodo.6707142 ...